Transport in times of an epidemic: Public transport measures in the Czech Republic and its regions - Martin Vrána; Simona Surmařová; Petr Hlisnikovský; Jiří Dujka (Review of Economic Perspectives, 2021)
In the first half of 2020, the global pandemic of the COVID-19 virus became a phenomenon affecting all spheres of human life. Measures against the spread of the virus have led to restrictions in life in public spaces and have also affected the transport sector. These impacts consisted of two types - firstly, the number of connections was reduced due to a drop in transport demand, and secondly, it was necessary to comply with hygiene measures on the part of carriers and passengers. The impacts of these measures could be monitored at all spatial levels, from global to local. This paper deals with the course of the so-called first wave of the pandemic in the Czech Republic in relation to public transport and its organization. The aim of the paper is to provide an overview of these measures in relation to general government regulations and their subsequent implementation at the national, regional (county) and local (selected large cities) level. Furthermore, the paper uses three case studies to show what changes long-distance domestic transport has undergone on selected routes. There was a significant reduction in the number of long-distance connections, some lines were not operated at all, and of course, all cross-border connections were canceled. The paper covers the period from the turn of February and March 2020, when the measures began to take effect, to the end of May 2020, when almost all the adopted measures were gradually relaxed. The paper concludes with a summary of the basic features of the organization of transport during the validity of the special measures, as well as areas where significant changes took place and whose consequences may persist after the pandemic subsides.
Keywords: R40; R41; I18; 330; COVID-19; epidemic; public health; public transport; restrictions; soft measures